Strategi Kompositoris Grup Band Djiwoastra di tengah Persaingan Industri Musik Metal Indonesia - Agustian, Aji; Zulkarnain Mistortoify (Program Studi Etnomusikologi, Fakultas Ilmu Budaya, Universitas Mulawarman, 2025)
This article examines the compositional strategies of the musical group Djiwoastra in constructing a musical identity rooted in historical and cultural narratives of the Nusantara through the medium of metal music. Using an autoethnographic approach, the paper reflects the creator’s lived experience in the creative process. The musical exploration undertaken by the group not only blends sonic elements, but also presents a dialectic between traditional and modern aesthetics within musical structure. Through collaborative methods that take into account the technical and expressive limitations of each member, Djiwoastra’s works develop linear and narratively driven musical patterns contextualized within the spirit of Javanese cultural might. Traditional instruments such as the Gandrang Makassar, Puik-Puik, and Balinese Ceng-Ceng are not treated as mere ornamentation but are integrated as structural elements in crafting a hybrid and articulate musical identity. This article posits that Djiwoastra’s creative practice is not merely an aesthetic endeavor, but a cultural strategy oriented toward resisting the homogenization of global musical tastes by revitalizing local values within a contemporary musical framework.